Thermal Transport in Oblique Finned Micro/Minichannels - Fan, Y (Springer, 2015)
The main aim of this book is to introduce and give an overview of a novel, easy, and highly effective heat transfer augmentation technique for single-phase micro/minichannel heat sink. The specific objectives of the volume are to: Introduce a novel planar oblique fin microchannel and cylindrical oblique fin minichannel heat sink design using passive heat transfer enhancement techniques Investigate the thermal transport in both planar and cylindrical oblique fin structures through numerical simulation and systematic experimental studies. Evaluate the feasibility of employing the proposed solution in cooling non-uniform heat fluxes and hotspot suppression Conduct the similarity analysis and parametric study to obtain empirical correlations to evaluate the total heat transfer rate of the oblique fin heat sink Investigate the flow mechanism and optimize the dimensions of cylindrical oblique fin heat sink Investigate the influence of edge effect on flow and temperature uniformity in these oblique fin channels.